Persistent Issues with the Development of Halal Tourism in North Sumatera - Hefriansyah Hefriansyah; Asmuni Asmuni; Muslim Marpaung; Hendri Tanjung (Tazkia Islamic Finance and Business Review, 2020)
The present study aims to uncover the problems, aspects, solutions and strategies of halal travel and tourism in North Sumatera, Indonesia. This study employs Analytic Network Process (ANP) methods in three steps, first, problem decomposition, pair-wise comparison questionnaire, and synthesis and analysis. ANP also used to gather the opinion and responses from the experts. From this study, it was found that the problems of improving halal travel and tourism based on their level of significance are as follows: Environment, Access and Services, and Communication. Meanwhile, the priority of aspects to improve halal travel and tourism based on their level of significance are environment, access, services, and communication. Similar to problems and aspects, solutions based on their level of significance are environment, access, services and communication. In addition, top three strategies that recommended from this study are ecosystem, destination, and accessibility and connectivity. The findings of this study are also furnished with some recommendation from the industry perspective and stakeholders of halal travel and tourism.